1984
DOI: 10.1111/j.1365-2125.1984.tb02567.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein binding and the role of increased alpha 1‐acid glycoprotein in moderately obese male subjects.

Abstract: Serum protein and lipid concentrations as well as the serum protein binding of propranolol, diazepam and phenytoin were measured in normal weight and obese volunteers. Concentrations of alpha 1‐acid glycoprotein (AAG) in the obese subjects were double that of the lean controls. Conversely, concentrations of high density lipoproteins (HDL) were decreased in the obese group. The serum binding of propranolol was increased in the obese subjects and correlated with serum AAG concentrations. Diazepam binding was sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 16 publications
(22 reference statements)
1
55
0
1
Order By: Relevance
“…Circulating ORM levels in our study group were more than twice the average levels reported in healthy people (Fournier et al, 2000). A previous study involving morbidly obese females and moderately obese males also showed that ORM protein concentrations were doubled compared to lean controls (Benedek et al, 1983;1984). We also showed previously that serum ORM levels were significantly elevated in obese people as compared to healthy people (Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…Circulating ORM levels in our study group were more than twice the average levels reported in healthy people (Fournier et al, 2000). A previous study involving morbidly obese females and moderately obese males also showed that ORM protein concentrations were doubled compared to lean controls (Benedek et al, 1983;1984). We also showed previously that serum ORM levels were significantly elevated in obese people as compared to healthy people (Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…In the ATV/RTV group, female participants had a higher median BMI than the male participants, and both participants with BMI >40 were female. In this analysis, RTV protein binding was shown to be sensitive to BMI, but not ATV or EFV; in the PK literature, the relationship between obesity and protein binding has not been clearly delineated, although it is postulated that alpha‐1 acid glycoprotein concentrations, to which RTV binds, are increased in obesity 43, 44, 45. This may also be a function of sex differences, as BMI and sex are linked, and our sample size is moderate.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, other inflammation markers such alpha 1 acid glycoprotein (AAG) and alpha 1 antitrypsin (AAT) have been found to be increased in obesity. [9][10][11] We therefore assessed the relationships between several circulating acute phase proteins, that is, CRP, AAG, fibrinogen (Fg) and AAT levels and both circulating and adipose tissue leptin, IL-6, TNFa and plasminogen activator inhibitor (PAI)-1 content in obese women.…”
Section: Introductionmentioning
confidence: 99%